Ayat-ayat Hukum dalam Pemikiran Mufasir Indonesia (Studi Komparatif Penafsiran M.hasbi Ash-shiddieqi dan M.quraish Shihab) - Ismatulloh, A.M. (FENOMENA, 2014)
The objectives of this study are to explain the tafseer of M. Hasbi Ash-Shiddieqi and M. Quraish Shihab about the law in Alquran. The researcher analyzed comparatively the two mufassir tafseer. The laws in Alquran analyzed, in this study, are about handcutpunishment, zina, and moslems hijab. The researcher used descriptive comparative research design. The sources of the data were Tafsir Alquranul Majid An-Nur which was written by M. Hasbi Ash-Shiddieqy and Tafsir Al-Misbah which was written by M. Quraish Shihab. The finding shows that Hasbi and Quraish Shihab tafseer about QS.Al-Maidah (38) consists of lawsuits. They wrote that the thief, in QS Al-Maidah, is one who steals things for many times. These two mufassir does not have any differences in interpreting QS Al-Maidah (38). However, the tafseer of Quraish Shihab seems to be more details and wide than the tafseer of Hasbi is. The two mufassir said that handcut punishment can be applied if there is not other way to resolve it. QS.An-Nur: 2, according to Hasbi dan Quraish Shihab, consists of firmly lawsuits for one who commited doing zina, that is, scourging 100 times. Hasbi argues that this scourging is for married man/woman. It is different to Quraish Shihab since it is for unmarried man/woman. For those who are called muhsan.muhsanah, they are punished by scourging to the death. Quraish Shihab claims that this scourging is hard to execute since it needs a confession from the person who commited to crime and it should fulfilled a special strict conditions. In terms of Moslem hijab, in QS Al-Ahzab: 59, Hasib stated that it is an obligatory. It should be dressed respectifully and particulary it was applied for the wives of prophet. Quraish Shihab argues that hijab is not an obligatory for Moslems women. He claims that it is a traditional custom of Arab women.